Blockchain sebagai Katalis Akuntabilitas Organisasi: Bukti Mediasi dari Kualitas Laporan Keuangan - Lisa Erfi Yunita; Janti Soegiastuti; Imelda Dea Savila; Vinsent Brilian Adiguna (Jurnal Proaksi, 2026)
Main Purpose - This study aims to analyze the effect of blockchain technology implementation and financial reporting quality on corporate performance accountability, using a mediation model approach.Method - Data were collected through a survey and analyzed using the Maximum Likelihood (ML) method within a structural modeling framework.Main Findings - The findings reveal that blockchain implementation does not have a significant direct effect on accountability. However, it significantly enhances the quality of financial reporting. Furthermore, financial reporting quality has a significant impact on accountability and fully mediates the relationship between blockchain and accountability. These results suggest that blockchain serves as a catalyst for improving accountability, but its effectiveness depends heavily on the quality of the financial reporting system.Theory and Practical Implications - The study contributes theoretically by reinforcing the mediating role of reporting quality in the context of digital transformation. Managerial implications highlight the importance of strengthening financial reporting systems as a foundation for optimizing the benefits of blockchain technology in enhancing organizational accountability. Novelty - This study contributes empirical evidence by examining the mediating role of financial reporting quality in linking blockchain technology adoption to performance accountability, a relationship that remains underexplored in the context of developing countries.